Implementation of Ijab Qabul with One Breath Perspectives of the Imams of the Mazhab and Sheikh Muhammad Arsyad Al-Banjari in Kitab An-Nikah - Fauziah Nuraini, Dewi; Nor Laily, Ana; Hifzi, Muhammad (Al-Mahkamah: Islamic Law Journal, 2024)
This study explains how the real truth of ijab  qabul in the midst of the controversy of the many claims for the execution of the ijab with a single breath which happened at Rizky Febian and Mahalini’s marriage contract. This research is a qualitative research method with descriptive analysis by describing the data obtained through words rather than in the form of numbers. Using library research as a source of data that the author then uses to determine the relevant legal provisions and the actual principles of the reality that occurs so that it can present legal answers to the problem digged. The results of the study showed that when analysed with the opinion according to the Sheikh Muhammad Arsyad Al-Banjari in the Book of An-Nikah, as well as the opinions of the priests of Mazhab, there is no provision explicitly regulating and also absolute on the claim to façade the ijab qabul in a breath and there are no provisions prohibiting it. Thus, it can be said that the execution of ijab qabul with one breath and must be connected with the law is jaiz, that is, can be done and can be left as long as it does not violate the existing provisions and this is also not an absolute condition in the implementation of ijab qabul, so affecting to touch the validity of an obstacle.